TELECOMMUNICATION AND COMPUTER SYSTEMS: TELECOMMUNICATION NETWORKS AND DEVICES - Kerimov Nihat (Web of Journals Publishing, 2025)
In recent times, information and communication technologies (ICT) and computer systems play a foundational role in the information environment. This article analyzes the concept of telecommunication, the development stages of networks, the functional role of telecommunication devices, and their integration with computer systems. The rapid development of telecommunication technologies has not only met society’s growing information demands but has also led to significant innovations in the economy, education, healthcare, and security sectors. Furthermore, the use of wireless communication, fiber-optic lines, satellite communications, and cloud-based network technologies in modern telecommunication networks is examined.
Keywords: Telecommunication, computer systems, networks, communication devices, information technologies.